Protein kinase A directly phosphorylates metabotropic glutamate receptor 5 to modulate its function - Uematsu, Ken (J Neurochem, 2015)
Metabotropic glutamate receptor 5 (mGluR5) regulates excitatory postsynaptic signaling in the central nervous system (CNS) and is implicated in various CNS disorders. Protein kinase A (PKA) signaling is known to play a critical role in neuropsychiatric disorders such as Parkinson’s disease, schizophrenia and addiction. Dopamine signaling is known to modulate the properties of mGluR5 in a cAMP- and PKA-dependent manner, suggesting that mGluR5 may be a direct target for PKA. Our study identifies mGluR5 at Ser870 as a direct substrate for PKA phosphorylation and demonstrates that this phosphorylation plays a critical role in the PKA-mediated modulation of mGluR5 functions such as extracellular signal-regulated kinase (ERK) phosphorylation and intracellular Ca(2+) oscillations. The identification of the molecular mechanism by which PKA signaling modulates mGluR5-mediated cellular responses contributes to the understanding of the interaction between dopaminergic and glutamatergic neuronal signaling.